2016
DOI: 10.1093/trstmh/trw011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a conditional cash transfer programme on TB cure rate: a retrospective cohort study in Brazil

Abstract: Although further research is needed, this study suggests that conditional cash transfer programmes can contribute to improve TB cure rate in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 28 publications
6
101
1
9
Order By: Relevance
“…[15][16] These results need to be confirmed elsewhere, but corroborate the importance of the adoption of Pillar 2 (social protection) in conjunction with Pillar 1 (integrated and patient-centered care) and Pillar 3 (research and innovation) for TB elimination, as proposed in the 2015 National TB Research Agenda for Brazil in 2015 45 .…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…[15][16] These results need to be confirmed elsewhere, but corroborate the importance of the adoption of Pillar 2 (social protection) in conjunction with Pillar 1 (integrated and patient-centered care) and Pillar 3 (research and innovation) for TB elimination, as proposed in the 2015 National TB Research Agenda for Brazil in 2015 45 .…”
mentioning
confidence: 59%
“…Recently, clinical and operational research have indicated that the approaches are more effective when they respond to local socio-cultural characteristics, organization of health service delivery, and type of community activities. These approaches should cover the cascade of actions that include local TB transmission control, screening, and diagnostic investigation of active and latent TB, followed by its antimicrobial treatment, incorporating biomedical approaches [9][10][11][12][13] , biopsychosocial 8,14 , strengthening social protection 15,16 , community participation 17 , and political commitment 18 . However, in high TB burden countries, operational research performed to cover such approaches are limited.…”
mentioning
confidence: 99%
“…Twelve studies presented patient or treatment supporters directed financial interventions (among then seven quasi-experimental studies), including monetary incentives 22,24,25,27,28,29,35,39,40,41 , a conditional cash transfer program 42 and economic support by voucher delivery 43 . Some studies 22,27,28,35 combined financial and non-financial interventions.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study linking the SINAN-TB database and the Single Registry (Cadastro Único -CadÚnico) database, suggests that those under treatment for TB and who are also enrolled in the Brazilian Program of conditional cash transfer, known as the Family Income Transfer Program (Programa Bolsa Família -PBF), obtained better results, reaching a proportion of cure 5.2% higher than the corresponding proportion among those not benefited by PBF. 9 In spite of the efforts to reduce the extent of TB-related inequalities among vulnerable groups and the general population, the impact of conditional cash transfers requires further confirmation in prospective studies.…”
Section: Can Brazil Achieve the New Who Global Targets For Tb Control?mentioning
confidence: 99%